2020
DOI: 10.3389/fmicb.2020.02111
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mRNA Stability During Bacterial Stress Responses

Abstract: Bacteria have a remarkable ability to sense environmental changes, swiftly regulating their transcriptional and posttranscriptional machinery as a response. Under conditions that cause growth to slow or stop, bacteria typically stabilize their transcriptomes in what has been shown to be a conserved stress response. In recent years, diverse studies have elucidated many of the mechanisms underlying mRNA degradation, yet an understanding of the regulation of mRNA degradation under stress conditions remains elusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 332 publications
(452 reference statements)
1
55
0
Order By: Relevance
“…Indeed most of these genes remain expressed at high level ('CAT-3' or 'CAT_4') but below a threshold classically associated with boundaries (a string of genes with above 20 normalized reads per kb, Supplementary Table 5). Moreover, we cannot exclude the possibility that some of these transcripts are stable RNAs produced in exponential rather than stationary phase 43 . This loss of boundaries in the central compartment is reminiscent of the phenomena observed in eukaryotes during G1-to-mitosis transition 44 and could reflect a more general phenomenon of genome compaction during the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed most of these genes remain expressed at high level ('CAT-3' or 'CAT_4') but below a threshold classically associated with boundaries (a string of genes with above 20 normalized reads per kb, Supplementary Table 5). Moreover, we cannot exclude the possibility that some of these transcripts are stable RNAs produced in exponential rather than stationary phase 43 . This loss of boundaries in the central compartment is reminiscent of the phenomena observed in eukaryotes during G1-to-mitosis transition 44 and could reflect a more general phenomenon of genome compaction during the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…These are generally located within the terminal arms, Supplementary Table 5). Moreover, we cannot exclude the possibility that some of these transcripts are stable RNAs produced in exponential rather than stationary phase 43 . This loss of boundaries in the central compartment is reminiscent of the phenomena observed in eukaryotes during G1-to-mitosis transition 44 and could reflect a more general phenomenon of genome compaction during the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Since the putative regulatory transcriptional sequences of the wild type and mutant genes are the same, this suggests that the increase in wild type transcript was not due to transcriptional up-regulation. It has been proposed that recognition of a nonsense mRNA could depend on translation [ 52 ] and that mRNA depletion is a consequence of the appearance of long tracts of mRNA that are unprotected by scanning ribosomes [ 28 ], which, by binding to the mRNA, have a protective effect on its stability [ 53 ]. Thus, we explain the higher amounts of fucA mRNA with an increment of translating ribosomes, which stabilize fucA mRNA and lead to the increased transcript level revealed by Real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing demand of α- l -fucosidase in the presence of xyloglucan oligosaccharides was not surprising. Several α- l -fucosidases belonging to glycoside hydrolases family GH29 in the Carbohydrate Active enZYmes database ( (accessed on 4 March 2021)) [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. In addition, we have previously reported that in S. solfataricus the α-xylosidase XylS and the β-glycosidase Ssβ-gly, hydrolyzed tamarind seed xyloglucan oligosaccharides in vitro [ 48 ].…”
Section: Discussionmentioning
confidence: 99%